manajemen masjid namira lamongan serta dampaknya terhadap jamaah menurut maqashid syariah - Nanda Nur Novadina; Irham Zaki (Universitas Airlangga, 2019)
This research aimed to find out what the takmir's management of Namira mosque was and its impact on society based on maqashid Syariah perspective. It based on the phenomenon that happened in the research object. The research object was the Namira mosque, which is located in Jotosanur village, Lamongan. This research used a qualitative method with a descriptive approach. After interviewing, the results of the research were analyzed by using descriptive data analysis technique. The result of the research showed that how much the operational funds were that takmir of Namira mosque needed, and it was not very often that lack of funds was covered by the family foundation of Namira mosque. Then, the impact caused by the implementation of Rupiah zero-balance that the funds were used to donate to the activities taking place in the Namira mosque has been fulfilled based on maqashid Syariah.Keywords: Infaq, Mosque, Welfare, Maqashid Syariah.REFERENCESAl-Qur’an danTerjemahannya. 2013. Departemen Agama Republik Indonesia. Arifin, Gus. 2016. Keutamaan Zakat Infak, Sedekah. Jakarta: PT. Elex Media Komputindo.Bungin, Burhan. 2005. Metodologi Penelitian Kualitatif: Komunikasi, Ekonomi, dan Kebijakan Publik serta Ilmu-Ilmu Sosial Lainnya. Jakarta: Kencana.Fauzia, Ika Yunia Dan Abdul Kadir Riyadi. 2014. Prinsip Dasar Ekonomi Dasar Islam Perspektif Maqashid Al Syariah. Jakarta: Kencana. Hafidhuddin, Didin. 2007. Agar Harta Berkah Dan Bertambah. Jakarta: Gema Insani Press.ICMI Orsat Cempaka Putih, Fokkus Babinrohis Pusat. 2004. Pedoman Manajemen Masjid. Jakarta: Yayasan Kado Anak Yatim. Sholihin, Ahmad Ifham. (2010). Buku Pintar Ekonomi Syariah. Jakarta: Pt. Gramedia Pustaka Utama. Shidiq, Sapiuddin. 2011. Ushul Fiqh. Jakarta: Kencana.Yin, Robert K, 2003. StudiKasus: Desain Dan Metode. Jakarta: Raja GrafindoPersada.Sumber Berasal dari Internet:bps.go.id: September: 2018simas.kemenag.go.id: Februari: 2018